PENGARUH PROFITABILITAS, DEBT COVENANT DAN MEKANISME BONUS TERHADAP TRANSFER PRICING: Studi Empiris Pada Perusahaan Sektor Barang Baku di Bursa Efek Indonesia - Sari, Dyah Ayu Mawar; Djohar, Chaidir (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
This study aims to find out and provide empirical evidence on the Influence of Profitability, Debt Covenant and Bonus Mechanism on Transfer Pricing in Raw Goods Sector Companies listed on the IDX for the period 2016-2020. The type of research used is quantitative (secondary) research that is causally comparative. The number of samples in this study was 50 observational data from 10 raw goods sector companies period 2016-2020 obtained using purposive sampling methods based on predetermined criteria. The data used is secondary data in the form of annual financial statements that have been audited in the period 2016-2020 obtained from the official website of the IDX. Technical data analysis used is descriptive statistics and regression analysis of panel data using Eviews-9 software. The results of this study are based on partial tests with the T-Test stating that Profitability has no significant effect on transfer pricing, Debt covenant has a significant effect on transfer pricing and Bonus mechanism has no significant effect on transfer pricing. Based on simultaneous tests with F-Test states that profitability, debt covenants and bonus mechanisms do not have a simultaneous and significant influence on Transfer Pricing